2011
DOI: 10.1164/rccm.201107-1239oc
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Vitamin D, Disease Severity, and Airway Remodeling in Children with Asthma

Abstract: Rationale-Little is known about vitamin D status and its effect on asthma pathophysiology in children with severe, therapy-resistant asthma (STRA).Objectives-Relationships between serum vitamin D, lung function, and pathology were investigated in pediatric STRA. Methods-Serum 25-hydroxyvitamin D [25(OH)D3 ] was measured in 86 children (mean age, 11.7 yr): 36 with STRA, 26 with moderate asthma (MA), and 24 without asthma (control subjects). Relationships between 25(OH)D 3 , the asthma control test (ACT), spirom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
279
5
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 299 publications
(346 citation statements)
references
References 34 publications
27
279
5
12
Order By: Relevance
“…Our own studies have addressed this in a severe therapy-resistant pediatric asthma cohort. We observe highly significant associations between serum 25-hydroxyvitamin D3 levels with lung function, asthma severity, and control [21]. Using this unique patient cohort, we recorded a positive correlation between serum 25-hydroxyvitamin D3 levels with the frequency of CD25 + Foxp3 + T cells in the airways, complimenting our in vitro observations.…”
Section: Discussionsupporting
confidence: 85%
“…Our own studies have addressed this in a severe therapy-resistant pediatric asthma cohort. We observe highly significant associations between serum 25-hydroxyvitamin D3 levels with lung function, asthma severity, and control [21]. Using this unique patient cohort, we recorded a positive correlation between serum 25-hydroxyvitamin D3 levels with the frequency of CD25 + Foxp3 + T cells in the airways, complimenting our in vitro observations.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have pointed out striking links in populations between vitamin D deficiency and asthma severity or requirements for anti-inflammatory medication (27)(28)(29)(30). In previous studies investigating the immunological basis of this relationship, we have shown that 1 α,25-dihydroxyvitamin D3…”
Section: Introductionmentioning
confidence: 73%
“…This arises in part from studies demonstrating that patients with poorly controlled asthma and/or poor responsiveness to corticosteroid have significantly reduced vitamin D, at least as assessed by the circulating precursor 25-hydroxyvitamin D3 (27)(28)(29)(30)47). We and others have previously demonstrated an association with 25(OH)2D3 status and airways smooth muscle mass (27,28,48). Bronchial smooth muscle hypertrophy and hyperplasia are prominent features of airway remodelling as is subepithelial fibrosis, and IL-17A is a key mediator implicated in lung structural changes with pro-fibrotic activity within the bronchial epithelium (45).…”
Section: Nanzer Et Al 15mentioning
confidence: 99%
“…This study, however, showed a significant inverse association between vitamin D and serum IgE, as well as vitamin D and daily inhaled corticosteroid dose in the pedia tric asthma group only (17) . Among the non casecontrol studies that reported significant inverse correlation with asthma severity, one study evaluated 616 asthmatic patients (13) , another studied 75 asthmatic patients (14) , whereas a third study investigated 86 asthmatic patients (16) . Therefore, more carefully designed studies are needed to clarify the relationship between asthma seve rity and vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from northern Italy showed a direct correlation between asthma control and serum 25(OH)D in a cohort of asthmatic children (14) . Other cross-sectional studies in children have shown that serum 25(OH)D concentrations are directly correlated with pulmonary function parameters, such as forced expiratory volume in one second (15) , and also inversely correlated with asthma severity and airway smooth muscle mass (16) .…”
Section: Introductionmentioning
confidence: 92%